Paleomagnetism Of 1780-1770 Ma Mafic And Composite Intrusions Of Smaland (Sweden): Implications For The Mesoproterozoic Supercontinent - Pisarevsky, S. A.; Bylund, Göran (American Journal of Science, 2010)
We present a paleomagnefic study of 1785 to 1770 Ma composite and mafic intrusions in Smaland, Sweden. A positive inverse baked contact test suggests the primary nature of their magnetization. The palaeomagnetic pole (45.7 degrees N, 182.7 degrees E, A(95)=8.0 degrees) may be regarded as a key pole for Fennoscandia. Available paleomagnetic data suggest that Laurentia and Fennoscandia/Balfica drifted together since 1780 Ma until at least 1265 Ma. These two continents could form a core of a hypothetical Mesoproterozoic supercontinent.